(untitled) (Olhar de Professor, 2023)
: In 2017, the National Curricular Common Core (BNCC) for Elementary Education was approved. The BNCC is characterized by being a document that guides the curricula, standardizing essential skills and abilities that students must develop throughout Basic Education. Given this scenario, this study has aimed to investigate what the authors of Education in Sciences say, in the National Curricular Common Core (Elementary School stage). This is a bibliographical review in the magazines in the area of Education, in the Google Scholar database and in the Theses and Dissertations portal of Capes, with the descriptors: “Base Nacional Comum Curricular” (National Curricular Common Core) and “Ensino de Ciências” (Science Teaching”, between the years 2017 - 2021. The results indicate that most of the authors in Science Education declare that it is a conservative and political text that does not meet the demands of the area, of a more human, plural and aware formation of the environment.